Case Report: Scleral hyperpigmentation associated with oral hydroxychloroquine use - Maretz, Caroline; Omoruyi, Felix; Wozniak, Rachel A. F. (Frontiers in Ophthalmology, 2023)
Hydroxychloroquine (HCQ) is a commonly used medication for its immunosuppressive and dermatologic effects. It has known ocular side effects, which include retinopathy, corneal deposits, and choroidal thinning. Herein, we report the first known case of HCQ-induced hyperpigmentation of the sclera. A 75-year-old female presented after 10-months of gradual progression of painless, blue-gray discoloration of the bilateral sclera, fingernails, and lower extremities secondary to oral HCQ therapy. Cessation of the drug led to a partial reversal of the hyperpigmentation at five-months, further supporting HCQ as the causative agent. Hyperpigmentation reactions can be distressing to patients and lead to decreased medication adherence, and given the widespread use of HCQ, it is important to increase awareness of this potential drug reaction.